Descriptive qualitative study of breathlessness and its management of Turkish individuals with self-reported heart failure - Simon Stewart; Mark C Petrie; Bridget Margaret Johnston; Muzeyyen Seckin (BMJ Open, 2024)
Aims To explore the experiences of individuals with heart failure, with a specific focus on elucidating the full spectrum of symptoms experienced and their subjective descriptions of breathlessness and self-management strategies regarding socio-cultural-behavioural context.Design Qualitative descriptive study underpinned by critical realism and situation-specific theory of heart failure self-care.Setting Participants from various settings (hospitals and community) in Southeastern Türkiye.Participants Adults reporting heart failure and breathlessness.Methods Semi-structured interviews were carried out with 20 individuals (11 women and 9 men). Data were audio-recorded and transcribed. Participants were asked to describe their symptoms, experiences with breathlessness, self-management strategies and health needs from their perspectives. The interview data were analysed using reflexive thematic analysis.Results There were a range (31 physical and 7 psycho-social behavioural) of symptoms experienced by participants. This included fatigue, difficulty sleeping, pain (not including chest pain) and fear about death and dying. Based on reflexive thematic analysis of semi-structured interviews, six main themes were identified. First two themes (knowledge and misconception, and experience of breathlessness) were related to breathlessness experience and knowledge. The third theme (culture and religious consideration) highlighted the importance of cultural and religious perspectives in breathlessness regarding Turkish socio-cultural-behavioural context. Themes four (breathlessness self-management/physical) and five (breathlessness self-management/psychological) were identified as self-management strategies for breathlessness. The need for improved health behaviours (improved health behaviours) was also identified.Conclusion Breathlessness and self-management strategies are affected by individual perspectives in relation to their socio-cultural-behavioural context. Understanding individuals’ unique breathlessness experiences regarding their socio-cultural-behavioural context assists in the identification of possible individualised-care strategies to improve their life and care quality in heart failure. We recommend creating a person-centred symptom assessment strategy with reference to culture or transculture guided by nurses. This will help to understand individuals’ unique symptom profiles and tailor responses to their needs.